Pengaruh Urbanisasi, Keterbukaan Perdagangan, Pertumbuhan Ekonomi, dan Pendidikan terhadap Konsumsi Energi Terbarukan di ASEAN-5 - Nurul Sa'adah; Choya Tia Rosalia, Amelia (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Reducing dependence on fossil fuels has become a global urgency in response to climate change. Renewable energy is seen as a sustainable alternative, but the social and economic determinants that influence its consumption in developing countries, particularly in ASEAN, have not yet been fully explored. This study aims to analyze the influence of urbanization, trade openness, economic growth, and education on renewable energy consumption in five ASEAN countries (Indonesia, Malaysia, the Philippines, Thailand, and Vietnam) during the period 1990–2021. Secondary data were obtained from the World Bank and UNDP and analyzed using a quantitative approach through panel data regression with Fixed Effect Model (FEM) approach using EViews 12 software. The estimation results show that urbanization has a positive and significant effect, where a 1% increase in urbanization increases renewable energy consumption by 0.33%. Conversely, trade openness and economic growth exhibit negative and significant effects; a 1% increase in each reduces renewable energy consumption by 0.10% and 11.95%, respectively. Education, although negatively oriented, does not show a significant effect. These findings confirm that urban dynamics can accelerate the adoption of clean energy technologies through systemic efficiency and infrastructure modernization, while the current orientation of economic growth and trade does not yet support the energy transition agenda in the region. This study provides important policy implications, particularly the need to reformulate low-carbon economic development strategies, optimize the potential of urbanization, and integrate energy education into long-term policies to strengthen renewable energy consumption in ASEAN-5.